Hubungan Pengalaman Belajar dan Kemampuan Pemecahan Masalah Matematis Siswa SMPK Sta. Maria Assumpta - Fernandez, Arnoldus; Lakapu, Meryani; Suci, Margareta (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to investigate the relationship between learning experiences and mathematical problem-solving skills of eighth-grade students at SMPK Sta. Maria Assumpta. This quantitative research employed questionnaires (Likert scale) with a specific number of items and mid-semester exam (SUMATIF) as data collection instruments from 25 students. The data normality test used the Kolmogorov-Smirnov test, and the Pearson correlation test was used to analyze the relationship between variables. The research results showed a significant negative relationship (p = 0.009; r = -0.511) between learning experiences and mathematical problem-solving abilities. The Cronbach Alpha reliability value was calculated to measure the internal consistency of the instrument. The implications of these results indicate that high learning experiences do not always correlate with increased problem-solving abilities. This study suggests the need to improve the quality of learning experiences and more effective learning approaches. The limitations of this study include the small sample size and the involvement of only two variables.